The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1039/b808772e
|View full text |Cite
|
Sign up to set email alerts
|

Large spectral tuning of a water–glycerol microdroplet by a focused laser: characterization and modeling

Abstract: Large spectral tuning of a water-glycerol microdroplet standing on a superhydrophobic surface by local heating with a focused infrared laser is studied both experimentally by optical spectroscopy and computationally using a lumped system formulation of the mass and heat transfer between the microdroplet and the chamber. The effects of optical scattering force, chamber humidity, size of microdroplet and laser power on the tuning mechanism are examined. The reversibility of the tuning mechanism is also studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…(18a) was obtained from Tu & Ray (2005) and Eq. (18b) from Kiraz et al (2008). Both simulated and measured results show that the size and water content of a droplet increase rapidly when the water vapor in the surrounding gas phase increases.…”
Section: Hygroscopic Growth Of Multi-component Dropletsmentioning
confidence: 79%
“…(18a) was obtained from Tu & Ray (2005) and Eq. (18b) from Kiraz et al (2008). Both simulated and measured results show that the size and water content of a droplet increase rapidly when the water vapor in the surrounding gas phase increases.…”
Section: Hygroscopic Growth Of Multi-component Dropletsmentioning
confidence: 79%
“…Figure 1 a considers on-axis illumination, i.e., the beam is focused at the center of the microdroplet. WGMs are therefore not excited in this configuration; only low quality oscillations corresponding to Fabry-Perot resonance modes are observed (Kiraz et al 2008). This experimental configuration allows for almost linear and reversible size tuning of the microdroplets and is used for the photothermal tuning spectroscopy experiments described in Section 4.…”
Section: Modelization and Simulationmentioning
confidence: 95%
“…We have recently demonstrated that photothermal tuning can be used in large, almost reversible spectral tuning of the whispering gallery modes (WGMs) of liquid microdroplets (Kiraz et al 2008. We have also demonstrated that a hysteretic behavior can be observed in a photothermal tuning cycle when the infrared laser is focused near the rim of the microdroplet, enabling bistable operation ).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Experimental studies on local heating in the focus of an optical trap have been hitherto reported for various systems. [6][7][8][9][10][11][12][13][14][15][16][17][18] However, the number of the reports on estimation of the amount of heat generation through absorption of a photon energy by single optically-trapped water droplets in air is still limited. [14][15][16][17][18] In order to achieve the quantitative measurement of temperature elevation of opticallytrapped water droplets in air, we employed a 1064-nm laser beam as a heating light source.…”
Section: Introductionmentioning
confidence: 99%